Energy audit in Block 5 at Tower Science and Technology (S&T) in UiTM Shah Alam towards energy efficiency / Mohammad Azhari Yusop - Yusop, Mohammad Azhari (2013)
This report presents energy audit in Block 5 at Tower Science and Technology (S&T). The main purpose of this research is to study on energy consumption and to give recommendations to reduce the energy wastage in the building. The energy waste can be determined by analyzing the energy consumption data that were recorded using Fluke Meter 1750 that was installed at the Distribution Board at Block 5.